Breadth and depth outreach of Islamic cooperatives: do size, non-performing finance, and grant matter?. Issue 7 (July 2020) - Wasiaturrahma,; Ajija, Shochrul Rohmatul; Sukmana, Raditya; Sari, Tita Novita; Hudaifah, Ahmad
Abstract: This study aimed to calculate the breadth, depth, and overall outreach score with case studies of several Islamic cooperatives in East Java. Generally, the level of this outreach is not too high, but it continuously showed an increase from 2014 to 2018. Those cooperatives with relatively small assets tend to have high outreach scores. Meanwhile, those with large assets have a lower outreach level. Therefore, this study utilized the Tobit regression analysis in order to investigate the factors that influence outreach score. The results showed that size, non-performing financing (NPF), number of branches, grants, financial leverage, and age have a significant impact on Islamic cooperatives' outreach. An interesting finding is that size has a negative effect. This is in contrast with the spirit to develop cooperatives in Indonesia. Also, a high NPF can significantly decrease the level outreach. Meanwhile, the increase in the number of grants appears to have a positive impact. Thus, through action research since 2012 and FGD on the management of Islamic cooperatives, this study provided an explanation on why these conditions can occur. Abstract : Breadth and Depth Outreach; Islamic Cooperatives; Size, Non-Performing Finance; Grant; Corporate finance; Financial economics; Behavioral economics; Social Inequality; Social Responsibility; Economics.